Studies on optoelectronic properties of magnetron Sputtered cadmium stannate (Cd2SnO4) thin films as alternative TCO materials for solar cell applications. Issue 2 (1st February 2018) - Sakthivel, P.; Murugan, R.; Asaithambi, S.; Karuppaiah, M.; Vijayaprasath, G.; Rajendran, S.; Hayakawa, Y.; Ravi, G.
Abstract: Single phase cadmium stannate thin films were deposited on glass substrates through rf magnetron sputtering by varying rf power and keeping substrates at room temperature. The effect of rf power on physical properties of the films and the correlations were systematically investigated. It has been found from XRD that structural phase transition occurred from amorphous to spinel structure with increase of rf power. AFM images revealed that the deposited films show smooth surface with nano grains. High transmittance was retained by the films in visible region and the band gap was decreased from 3.05 to 2.49 eV for increasing rf power by quantum confinement effect. The Mott-Davis model and drude model were used to evaluate the optical constants and free carrier absorption. The electrical resistivity of the films varied in three orders of magnitude as a function of rf power which could be explained by oxygen vacancies formation. From these results, the films deposited at 150 W has the low resistivity of the order of 10 −3  Ω cm with high optical transparency as 80% which could be the preferred conditions to deposit high quality films for future TCO layers for cadmium based CdTe/CdS solar cell devices.